PREFNEG: preference-based price negotiation scheme in fog environment. (7th October 2022) - Malukani, Shaifali P.; Bhensdadia, C.K.
Fog computing has emerged as a promising extension of cloud computing. Owing to recent developments, there has been a tremendous increase in the number of fog service consumers and providers who trade for fog resources. Consumers pay rent to the providers for utilisation of the fog resources. A dispute may exist for the announced rent as traders are interested in their financial gain. Price negotiation strategies help in solving this dispute and building long-term solutions. However, due to the heterogeneous nature of fog, QoS attributes significantly vary for a user-fog node association. So, entities may prefer each other based on attributes other than price. They want to get associated with the preferred trading partners at a negotiated price. This work presents a novel preference-based negotiation strategy for many to many, bilateral and concurrent negotiations in the fog environment. Results show that PREFNEG significantly increases the average user and fog utilities.